Algorithmic Authenticity: An Overview - Bounegru, Liliana; Devries, Melody; Harris, Amy; holtzclaw, hannah; Jucan, Ioana B; Juhasz, Alexandra; Kamish, D.W; Langlois, Ganaele; Proctor, Jasmine; Tomlinson, Christine; Vasudevan, Roopa; Weltevrede, Esther; et al. (meson press, 2023)
What makes information feel true or compelling in our contemporary digital societies? This book brings together different disciplinary understandings of “authenticity” in order to find alternative ways to approach mis- and disinformation that go beyond contemporary fact-checking and its search for the “authentic” truth. Patterned under the algorithmic flows of digital capitalism, authenticity itself is subject to variation, iteration, and outside influence. Linking cross-disciplinary research on the history and practices of algorithmic authenticity points to new research questions to understand the impact of algorithmic authenticity on social life and its role in contemporary information disorder.